2020
DOI: 10.3390/info12010007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclists’ Crossing Intentions When Interacting with Automated Vehicles: A Virtual Reality Study

Abstract: Most of cyclists’ fatalities originate from collisions with motorized vehicles. It is expected that automated vehicles (AV) will be safer than human-driven vehicles, but this depends on the nature of interactions between non-automated road users, among them cyclists. Little research on the interactions between cyclists and AVs exists. This study aims to determine the main factors influencing cyclists’ crossing intentions when interacting with an automated vehicle as compared to a conventional vehicle (CV) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our findings are in line with a simulator study by TRL [49], which reported that AV distinguishability had no significant effect on gap acceptance, a video‐based experiment by Dey et al. [50], which concluded that knowledge of a vehicle driving mode does not play a significant role in pedestrians’ crossing behaviours, and a study using a head‐mounted display which found that vehicle type did not have a significant impact on cyclists’ crossing intentions (Nuñez Velasco et al [51]). A possible reason for the lack of effect is that stickers and a lidar are hard to detect, as Experiment 2 showed.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with a simulator study by TRL [49], which reported that AV distinguishability had no significant effect on gap acceptance, a video‐based experiment by Dey et al. [50], which concluded that knowledge of a vehicle driving mode does not play a significant role in pedestrians’ crossing behaviours, and a study using a head‐mounted display which found that vehicle type did not have a significant impact on cyclists’ crossing intentions (Nuñez Velasco et al [51]). A possible reason for the lack of effect is that stickers and a lidar are hard to detect, as Experiment 2 showed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that the vehicle type affected the perceived risk, no significant difference was found in the crossing intention. However, pedestrians who did recognize the vehicle as an AV had, overall, lower intentions to cross (Nuñez Velasco et al, 2019). For cyclists, the gap size and the right of way were found to be the primary factors affecting the crossing intentions of the individuals.…”
Section: Vehicle Implicationsmentioning
confidence: 85%
“…Moore et al (2019) made a case against eHMIs and reported that implicit cues are dominant; they reported no significant differences in interaction quality for pedestrian-vehicle encounters at a crosswalk, with and without a driver. Several other studies concur that implicit communication is a more important cue than explicit signs, gestures, or other vehicle features (Clamann, Aubert, and Cummings 2017;Dey et al 2019;Lee et al 2020;Nuñez Velasco et al 2020;Rothenb€ ucher et al 2016).…”
Section: Introductionmentioning
confidence: 83%